Diversidade e biogeografia dos lagartos da Serra do Espinhaço - António Jorge do Rosário Cruz (2019)
We present distribution and natural history data for lizards from the Espinhaço, an ancient mountain range from Brazil. We gathered information on 95 lizards species based on the literature, museum collections, and field work. Most of this fauna is typical of open environments, terrestrial, diurnal, and oviparous. Gymnophthalmidae was the most representative family with 25 species, followed by Tropiduridae (19), Mabuyidae (11), Teiidae (10), Leiosauridae (8), Anguidae (7), Pyllodactylidae (6), Gekkonidae (5), Dactyloidae (1), Iguanidae (1), Polychrotidae (1) and Sphaerodactylidae (1). Among these lizards, 22.2% (n=20) are endemic from the municipalities encompassed by the Espinhaço. About 24% (n=19) are endemic from the Caatinga, 15% (n=12) from the Cerrado and 12% (n=9) from the Atlantic Forest. In this study, we point the Espinhaço as a place of extreme importance for biodiversity conservation. Among the recorded species, three were evaluated by the IUCN and the Brazilian government and States of Minas Gerais and Bahia as Critical Endangered, 15 as Endangered and six as Vulnerable. We present an annotated species list with natural history, ecology, and taxonomy information, including type locality, distribution, reproduction and other relevant data. A dichotomous key based on gathered taxonomic information of morphological characters/attributes is also presented.